2004
DOI: 10.3989/scimar.2004.68n2227
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal changes in dimethyl acetal (octadecanal) levels of <i>Octopus vulgaris</i> (Mollusca, Cephalopoda): relation to feeding ecology

Abstract: SUMMARY: The present study aimed to identify and quantify the dimethyl acetal (DMA) levels in the muscle of Octopus vulgaris Cuvier, 1797, and to investigate the possible influence of octopus feeding ecology on their spatial and seasonal variations. The research was performed over one year in three areas of the Portuguese coast: Viana do Castelo, Cascais and Tavira. Significantly higher values of DMA were detected in Tavira (p<0.05), an area where the importance of bivalves in the octopus' diet was higher. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 50 publications
0
7
0
3
Order By: Relevance
“…These results suggest that the exposure to PAHs in the NW Portuguese coast is moderate; however it must be taken into account that octopuses used in this study were captured around 10 km offshore and the contamination levels decrease with increasing distance from the pollution sources (Baumard et al, 1999). The high metabolism of PAHs in fish might have also contributed to the low levels found in the octopus digestive gland since Osteichthya species makes up a great part of the octopus diet in the NW Portuguese coast (Rosa et al, 2004a).…”
Section: Pah Levelsmentioning
confidence: 72%
See 1 more Smart Citation
“…These results suggest that the exposure to PAHs in the NW Portuguese coast is moderate; however it must be taken into account that octopuses used in this study were captured around 10 km offshore and the contamination levels decrease with increasing distance from the pollution sources (Baumard et al, 1999). The high metabolism of PAHs in fish might have also contributed to the low levels found in the octopus digestive gland since Osteichthya species makes up a great part of the octopus diet in the NW Portuguese coast (Rosa et al, 2004a).…”
Section: Pah Levelsmentioning
confidence: 72%
“…As referred above, the octopus diet in the NW Portuguese coast is constituted mainly of Osteichthya species (Rosa et al, 2004a) that directly absorb PAHs from the water column, supporting the greater contribution of LMW than HMW PAHs observed in the digestive gland of the octopus (Nakata et al, 2003;Perugini et al, 2007;Webster et al, 2002). Naphthalene was the most abundant PAH in the octopus digestive gland in the different sampling periods.…”
Section: Pah Levelsmentioning
confidence: 92%
“…Whereas the small amount of solutes meant it was not possible to unequivocally confirm the double-bond structure for 20:2 and 22:2 NMI, the 20:3 NMI was confirmed as Δ5,11,14 20:3. Dimethylacetals (DMA) of 16 and 18 carbons were also detected as previously described (Rosa et al 2004). …”
Section: Fatty Acid Composition Of Octopus Tissuesmentioning
confidence: 99%
“…Although some studies point out that benthic species tend to prey mainly on crustaceans while fishes predominate the pelagic species [95,96,97], others studies indicate that the prey spectrum in the diet is related to the most readily available prey (Table 2) [93]. For instance, Smale and Buchan [98] and Ambrose and Nelson [99] showed that octopus had a greater preference for bivalves, forming up to 88% of its diet.…”
Section: Cephalopod Life Strategies and Feeding Ecologymentioning
confidence: 99%
“…High variable DA levels, ranging from 1.1 to 166.2 μg DA g −1 were found in the digestive gland (DG) of the common octopus ( Octopus vulgaris ) off the Portuguese coast (Figure 7A; Table 1). The highest DA levels are observed in DG because this organ is the primary site of digestive absorption and intracellular digestion in cephalopods [93,111]. Thus, it may act as a DA reservoir, as it is for other substances (lipids, contaminants, etc .)…”
Section: Hab-toxins In Cephalopodsmentioning
confidence: 99%